2022
DOI: 10.1007/s11605-022-05398-7
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Analysis in the Management of Iatrogenic Bile Duct Injury During Cholecystectomy: a Nationwide Multicenter Study

Abstract: Background Iatrogenic bile duct injury (IBDI) is a challenging surgical complication. IBDI management can be guided by artificial intelligence models. Our study identified the factors associated with successful initial repair of IBDI and predicted the success of definitive repair based on patient risk levels. Methods This is a retrospective multi-institution cohort of patients with IBDI after cholecystectomy conducted between 1990 and 2020. We impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…One of the great challenges we currently face is to define the AI models that best represent our medical needs. Not only does it consist of data analysis, but the objective is also to integrate this type of methodology so that it has a logic in our daily surgical practice and allows us to make better decisions, especially in our more complex surgeries [ 3 6 ].…”
mentioning
confidence: 99%
“…One of the great challenges we currently face is to define the AI models that best represent our medical needs. Not only does it consist of data analysis, but the objective is also to integrate this type of methodology so that it has a logic in our daily surgical practice and allows us to make better decisions, especially in our more complex surgeries [ 3 6 ].…”
mentioning
confidence: 99%
“…There is significant potential for artificial intelligence and computer-guided technology in surgery for postcholecystectomy biliary stricture. Lopez-Lopez et al [ 33 ] demonstrated the use of machine learning to develop a risk-scoring model and improve the accuracy of predicting the success of surgical repair in managing iatrogenic BDI. Also, artificial intelligence and computer-guided technology could avoid misidentifying critical structures during minimally invasive BDI repair.…”
Section: Future Perspective – a New Era Of Bile Duct Repairmentioning
confidence: 99%
“…The treatment of BDI may vary from simple stenting of minor injuries to complicated surgical reconstruction in the case of major injuries. Roux-en-Y HJ is the preferred method for severe BDI, and a series of studies have shown good outcomes after this procedure 1 5 .…”
Section: Introductionmentioning
confidence: 99%